The Effect Of Implementation Digital Marketing, Product Quality And Product Innovation On Sales Volume Of UMKM Rokiku Balikpapan: Rahajeng Cahyaning Putri Cipto1 Hestiana Yudianti2 - ajeng cipto; Hestiana Yudianti (Jurnal Penelitian Ekonomi dan Akuntansi (JPENSI), 2023)
This study aims to determine the effect of digital marketing, product quality and product innovation on the sales volume of UMKM Rokiku Balikpapan. This type of research is quantitative. The data collection technique in this study was to use a questionnaire or google form. The population in this study are consumers who have made purchases at the Rokiku Balikpapan UMKM. By using a purposive sampling technique, so that the sample used is 100 respondents. The data analysis technique used was multiple linear regression using the SPSS Version 24 program. The results showed that digital marketing, product quality and product innovation simultaneously had a significant effect on sales volume at the Rokiku Balikpapan UMKM. Partially, each variable has a significant effect on sales volume at the Rokiku Balikpapan UMKM Keywords: Digital, Marketing, Product Quality, Product Innovation, Sales Volume